Preparation and characterisation of natamycin: gamma-cyclodextrin inclusion complex and its evaluation in vaginal mucoadhesive formulations - DURMUŞOĞLU, LÜTFİYE (ELSEVIER SCIENCE INC, 2008)
Novel formulations of vaginal bioadhesive tablets were prepared where the natamycin was complexed with gamma-cyclodextrin (NT-gamma CyD)to increase the solubility and stability of NT in aqueous solutions and reduce the side effects of the drug without decreasing antimycotic activity. Favourable interactions between the NT and gamma CyD and formation of the 1:1 inclusion complex were observed. The MIC90 of both NT alone and NT-gamma CyD complexes were below 0.0313 mu g mL(-1), suggesting that complexation with gamma CyD has effectively increased the antimycotic activity of NT, thus indicating the clinical usefulness of NT-gamma CyD complexes. The sustained drug release of NT was achieved to over 8 h periods by altering the polymer component of formulations which was responsible for differences in water absorption and erosion behaviour of the tablets. Bioadhesion studies have clearly indicated that enhancement of mucoadhesion was achieved by inclusion of Carbopol (R) 934P and by tailoring the ratio of Carbopol (R) 934P in the formulation, a high mucoadhesion to vaginal mucosa can be achieved. Hence, the formation of complex between NT and gamma CyD and effective combination with polymers attain a bioadhesive and sustained release formulation of NT suitable for vaginal delivery and the effective treatment of Candida infections. (C) 2008 Wiley-Liss, Inc. and the American Pharmacists Association.
Keywords: natamycin; gamma-cyclodextrin; inclusion complex; vaginal drug delivery; bioadhesion; hydroxypropyl methyl cellulose; xanthan gum; Carbopol (R) 934P; Candida spp; IN-VITRO; BETA-CYCLODEXTRIN; DRUG-DELIVERY; RELEASE; POLYMERS; TABLETS; SYSTEMS; SOLUBILIZATION; PACLITAXEL; SOLVATION